Community Participation Process in Community-Based Tourism Development in Waerebo Traditional Village, Manggarai Regency, Flores - Ary Sendjaja Suhandi; Evi Novianti; Dina Oktavia; Alexader M.A Khan; Wita P. Simatupang (ASEAN Journal on Hospitality and Tourism, 2022)
Waerebo traditional village is one of the villages in Flores that has managed to rise through tourism development. The tourism business in Waerebo is owned and managed by the community. This study aims to determine the process of community participation in the development of community-based tourism. This study uses a qualitative method. Primary data were collected through observation and in-depth interviews with institutions and parties involved in the development. Assistance with a participatory approach through the placement of facilitators to live with the community is carried out by partners from the Waerebo Cultural Conservation Institute. The training activities followed by practice by the community, accompanied by facilitators, have shown good results. The community is involved in all stages, from planning, implementing activities, and evaluating activities. Community participation from planning to implementation is essential in developing CBT and maintaining destination resilience. The CBT approach is able to increase people's income, help maintain traditional houses, forest roads, provide diesel and solar electricity, and improve their children's education.